Cafeteria food supply chain in Universiti Utara Malaysia - Abdul Aziz, Mohammad Hariri; Mohamed Udin, Zulkifli (2017)
The purpose of the research is to identify a food supply chain in Universiti Utara Malaysia cafeteria.Supply chain means a link between a factory and its supplier to produce a product or service.The systematic of the process food at large area are most important thinks.This is because, food once of needed in human living. The research is focusing on the cafeteria in University Utara Malaysia.The methodology of the research is qualitative method that is inquiring employed of marketing research include in-depth interviews with individuals and it is also can be in-context observation.In this research, qualitative is more relevant because the flow on supply chain from starting until the end can be explain by top manager.The findings of the research is to ensuring adequate food can be provided to students in a day, identify the demand and the requirements in accordance with the taste of food according to the students taste and identify improvements needed to strengthen the provision of food services to students.